Assessment of Comprehensibility of Industry Conflicts of Interest and Disclosures by Multiple Sclerosis Researchers at Medical Conferences - Martin, Sarah-Jane (JAMA Netw Open, 2021)
This cross-sectional study uses length of disclosure slide display times and slide word counts to assess the comprehensibility of industry conflicts of interest (COI) disclosures by researchers presenting at the world’s largest multiple sclerosis (MS) conference.